Prevalência das hepatites B e C e conhecimento das normas de biossegurança em profissionais de manicure/pedicuro de salões de beleza de Maringá, Paraná - Prado, Gabriela de Castro (2017)
Nowadays, a very common habit among women is to remove the cuticles from the hands and feet before enameling them. This activity is performed in salons by specialized professionals. Such conduct increases the degree of exposure to the Hepatitis B and C virus, due to the carelessness of professionals in handling non/poorly sterilized sharp objects. This study evaluated the prevalence of hepatitis B and C, sociodemographic data and knowledge about the biosafety of professionals from 30 salons in Maringá, Paraná. To identify the contamination of the professionals was performed in a rapid test for hepatitis B and C and, when reagent, confirmed in the research of HBsAg, anti-HBc, anti-HCV serological markers, make HBV-DNA and HCV-RNA. Identification of HBV and HCV genotypes was also made. A cross-sectional study was carried out with consecutive and serial sampling, for convenience of time and location, totaling 150 manicures. The manicure/pedicure professionals were submitted to a questionnaire to obtain epidemiologic and biosafety data. The data were considered significant adopting p <0,05. This work was approved by Ethics and Research Committe in Human Beings, under the opinion nº 1,573,796. All participants were female, with a mean age of 33 [25; 42,5] years. The mean working time was 11.73 ± 6.80 years. The level of schooling was 42 (28,0%), 89 (59,3%) and 19 (12,7%) participants for elementary, middle and high school, respectively. Based on two aspects, transmissibility and prevention, professionals' knowledge about hepatitis B and C was evaluated. Thus, 94 (62.67%) participants reported knowing both aspects and 56 (37.3%) only one or none them. Statistical analysis showed that the level of schooling was related to knowledge of the disease, vaccination and use of PPE (p <0,01), demonstrating that higher level manicures showed a greater awareness of the need to protect themselves (99%) in compare to the other groups. None of the professionals did the correct disinfection of the table of work, regardless of schooling and knowledge of the disease. The reuse of gloves was low among the participants in comparison with the majority who responded adequately about the need to discard the gloves between the attendances. Only one sample was tested for HBV and classified as genotype D. The prevalences of hepatitis B (0.7%) and C (0.0%) were low. Although Maringá's professional salon manicures / pedicures know the need for the use of PPE and the application of biosafety norms, such knowledge does not necessarily imply the preventive and safe practice of professionals.